2009
DOI: 10.1037/a0017901
|View full text |Cite
|
Sign up to set email alerts
|

Does a continuous feedback system improve psychotherapy outcome?

Abstract: Using outcome data on a continual basis to monitor treatment progress has been identified as a way to enhance psychotherapy outcome. The purpose of this study was to investigate the use of a continuous feedback assessment system, the Partners for Change Outcome Management System (PCOMS; Miller & Duncan, 2004). Findings from 2 client samples that attended individual therapy at a university counseling center (N = 74) or a graduate training clinic (N = 74) indicated that clients who used PCOMS with their therapis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
230
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(253 citation statements)
references
References 33 publications
(49 reference statements)
15
230
5
2
Order By: Relevance
“…The IPV literature indicates that the facilitator and offender relationship is a key component required for reduced recidivism, and when facilitators take a more active role through continuous assessment, they can readily identify clients who are not progressing in treatment and can intervene and assess why the client is not improving before the client terminates prematurely (Reese et al, 2009). Facilitative and supportive relationship roles, goal specificity, and goal agreement between the facilitator and client focused on strengths and solutions have been shown to facilitate change, to impact the client's experience in feeling cared about, seeing a way forward, valuing oneself, and building up trust, willingness to continue in the program and demonstrated recidivism reduction.…”
Section: Perpetrator Treatment and Practitioner-client Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPV literature indicates that the facilitator and offender relationship is a key component required for reduced recidivism, and when facilitators take a more active role through continuous assessment, they can readily identify clients who are not progressing in treatment and can intervene and assess why the client is not improving before the client terminates prematurely (Reese et al, 2009). Facilitative and supportive relationship roles, goal specificity, and goal agreement between the facilitator and client focused on strengths and solutions have been shown to facilitate change, to impact the client's experience in feeling cared about, seeing a way forward, valuing oneself, and building up trust, willingness to continue in the program and demonstrated recidivism reduction.…”
Section: Perpetrator Treatment and Practitioner-client Relationshipsmentioning
confidence: 99%
“…Of note is leaders serving as facilitator versus authority figures may more easily achieve successful recidivism reduction outcomes. Indeed, research suggests that when facilitators take a more active role through continuous assessment, they can readily identify clients who are not progressing in treatment and can intervene and assess why the client is not improving before the client terminates prematurely (Reese, Norsworthy, & Rowlands, 2009). Furthermore, Dilks, Tasker, and Wren (2013) suggest that the therapist's strategic effort to develop and maintain a relationship seemed to impact the client's experience in feeling cared about, seeing a way forward, valuing themselves, and building up trust in the therapist.…”
Section: Facilitator Educationmentioning
confidence: 99%
“…Utilizing continuous client feedback leads to fewer premature terminations, improved outcomes for clients at risk for termination (Brown & Jones, 2005;Whipple et al, 2003), increased opportunities to repair alliance ruptures, and improvements in the therapeutic relationship (Ackerman et al, 2001). Clients, both individuals and couples, using feedback mechanisms with their counselor demonstrate significantly greater treatment gains than those not receiving feedback (Anker et al, 2009;Miller et al, 2006;Reese et al, 2009a;Reese, et al, 2010). Reese and colleagues (2009a) reported that the feedback condition clients in one study achieved reliable change in fewer sessions than those in the no-feedback condition.…”
Section: Client Feedback Research Evidencementioning
confidence: 99%
“…Mental health practitioners have increased their use of continuous and direct client feedback mechanisms in response to the growing body of evidence supporting their use in treatment (Anker et al, 2009;Duncan & Miller, 2008;Lambert & Shimokawa, 2011;Miller, Duncan, Brown, Sorrell, & Chalk, 2006;Reese, Norsworthy, & Rowlands, 2009a;Reese et al, 2010). Utilizing continuous client feedback leads to fewer premature terminations, improved outcomes for clients at risk for termination (Brown & Jones, 2005;Whipple et al, 2003), increased opportunities to repair alliance ruptures, and improvements in the therapeutic relationship (Ackerman et al, 2001).…”
Section: Client Feedback Research Evidencementioning
confidence: 99%
“…19 Diabetes care managers have also successfully used the ORS and SRS with patients and have demonstrated improved diabetes-associated outcomes. 20 We believed that the use of the ORS and SRS in pharmacy practice might produce similar results as those shown in psychotherapy and would enhance the effectiveness of pharmacists' clinical services.…”
mentioning
confidence: 99%